Study of Furniture in Public Education in Relation to the User's Anthropometric Measurements. Case: UFPS Colombia (2018)
A study is presented on the ergonomic criteria associated with the university chair and the anthropometric measurements of the users. For this purpose, a study was carried out with a simple random sample of 376 students from the University Francisco de Paula Santander, two instruments were designed to collect the information, a perception survey that would show the discomfort and difficulties generated by the furniture, and an anthropometric study of the seated position; In addition, the dimensions of a random specimen were taken to make a typological evaluation in contrast with the NTC 4734, according to the results it was demonstrated that 100% of those surveyed said they suffer at least one discomfort due to the posture and materials of the university chair, the most significant pain is present in the buttocks, the current chairs are 9.09% smaller than allowed by the norm and according to the anthropometric requirements, the dimensions of the university chair should increase in proportion 14.2%. It is concluded from the information collected that the university chairs do not meet the ergonomic requirements of comfort and functionality.